The Discriminatory Use of the “KGB Procedure” by Police Against Women in Canada - Craig, Elaine (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2025)
In R. v. B. (K.G.) (KGB), the Supreme Court identified the procedural criteria necessary to ensure sufficient reliability of certain types of witnesses’ police statements, such that they can be introduced for the truth of their contents. The criteria include that the statement be videotaped, taken under oath, and that the witness be cautioned regarding the severe penal sanctions they could face if they lie. The type of witnesses contemplated are accomplices, coaccused, or others whose character makes them presumptively untrustworthy, and whose statement may become necessary because of the likelihood that they will recant at trial. The Court did not intend for KGB to be used generally, and the police do not typically impose this protocol on people who report crimes. Indeed, there are two types of witnesses subjected to KGB when they give statements to the police: those the Court intended (criminally implicated, coaccused or presumptively untrustworthy witnesses) and women who allege sexual or gender-based violence. A close examination of case law, the rules of evidence, and Crown prosecution standards reveal that imposing this protocol on women who allege sexual and other gender-based violence is, in the vast majority of cases, pointless, rooted in discriminatory assumptions about women and rape, and likely to impose unnecessary harms on those who turn to the criminal justice system to respond to experiences of sexualized violence.